Specific RNA-cleaving activities from HeLa cells. - Ferrari, S (Proc Natl Acad Sci U S A, 1980)
Subcellular fractionation of HeLa cells was carried out under gentle conditions to isolate enzymes that cleave RNA precursors in a specific manner. Four separate activities--cleavage of HeLa cell heterogeneous nuclear RNA, the HeLa cell 45S rRNA precursor, RNA . DNA hybrids (RNase H), and the Escherichia coli tRNATyr precursor (RNase P)--were revealed by these studies. The specificity and limited nature of these cleavages suggest that they are due to eukaryotic RNA-processing enzymes. The virtual absence of random nucleases from these enzymes was demonstrated by their inability to cleave the 8000-base early mRNA precursor of bacteriophage T7, E. coli 30S rRNA precursor, or HeLa cytoplasmic poly(A)-containing RNA. IMAGES: